Equity Care - Geskey, Joseph (The Hastings Center report, 2020)
An eight hundred-square-foot house greets me and a licensed practical nurse. We walk on uneven, disintegrating concrete steps before entering the patient's daughter's home, and we can see a haze of cigarette smoke before we enter the living room. Although the patient is old enough for retirement, she tells me that, if it were up to her, she would still be working. Noticing the medical equipment occupying her room—oxygen, pulse oximeter, and blood pressure machine—I am reminded that our health system is trying, like many other systems across the country, to manage people's chronic illness better by bringing technology into patients’ homes in hopes of preventing hospital readmissions. For this patient, the hope is that, if she gets symptoms that suggest another exacerbation of her chronic obstructive pulmonary disease, she can manage it herself. If I hadn't spent hundreds of hours in patients’ homes, I would have a low threshold for ordering home-based nursing and telehealth; it would often seem like a good solution.